Intermetallic compounds M2Pt (M = Al, Ga, In, Sn) in the oxygen evolution reaction. Issue 22 (18th October 2021) - Barrios Jiménez, Ana María; Ormeci, Alim; Burkhardt, Ulrich; Altendorf, Simone G.; Kaiser, Felix; Veremchuk, Igor; Auffermann, Gudrun; Grin, Yuri; Antonyshyn, Iryna
Abstract : The OER activity of isostructural M2 Pt (M = Al, Ga, In, Sn) compounds is governed by the nature of counterpart element (M), its leaching rate and corresponding change of the Pt electronic state. Abstract : Pt-based intermetallic compounds M2 Pt with anti -CaF2 type of crystal structure and counterpart elements (M) from groups 13 (Al, Ga, In) and 14 (Sn) were studied as electrocatalysts for the oxygen evolution reaction (OER) in acidic media. Polar covalent bonding M–Pt with substantial charge transfer makes the difference between M2 Pt and elemental platinum. The compounds M2 Pt (M = Al, Ga, In) possess enhanced OER activity compared to elemental Pt and it improves during the partial on-going leaching of the M component. Therefore, the M2 Pt compounds act as precursors for formation of OER-active M x Pt1− x layers.